Modeling the solutions for development of sport tourism in Iran - Hossein Abdolmaleki; Mehdi Babaei; Nazanin Rasekh; Michal Varmus (Research in Sport Management and Marketing)
Purpose: In marketing any strategy or action implemented should be closely tied to creating and development a positive image of tourism destination. The aim of this research was to investigate the factors related to the barriers to the development of sport tourism and its destination images in case of Mashhad city. Methods: The method of this applied research was descriptive-correlation. 87 professors and experts in sport management voluntary completed a questionnaire that Goldi Gouklani (2011) used it in her research. The construct validity was examined by confirmatory factor analysis. Reliability of research instrument was obtained 0.86 using Cronbach's alpha. At the level of inferential statistics, the normality of the data distribution was evaluated using Shapiro-Wilk test. Finally, confirmatory factor analysis and structural equation modeling was used to analyze the data.Results: Finding showed that: Problems of management and human resources have a significant role in the development of Mashhad sport tourism (β = 0.499, P < 0.001). Barriers of legal sponsor has a significant role in the development of Mashhad sport tourism (β = 0.21, P < 0.01). Marketing barriers has a significant impact on sport tourism (β = 0.19, P < 0.01). Problems and barriers of Infrastructures and facilities has a significant role in the development of Mashhad sport tourism (β = 0.25, P < 0.001). Weakness of research and study has a significant role in the development of Mashhad sport tourism (β = 0.17, P < 0.01). Finally, cultural and educational barriers have a significant role in the development of Mashhad sport tourism (β = 0.42, P < 0.001). Conclusion: Therefore, planning for solving problems and developing sport tourism and destination images seems to be essential.